Development of Ways to Improve the Energy Efficiency of Residential Buildings with Reinforced Concrete Tank Walls - Miralimov Mirrakhim Mirmakhmutovich; Adizov Bobur Barotovich; Mamadaliyev Zukhriddin Rakhimjanovich (Zien Journals, 2022)
The book is devoted to an important and relevant direction in the development of modern construction - energy-efficient reinforced concrete structures of buildings.
Keywords: Energy saving in the production; construction and operation of basic building materials; Energy-saving synthetic geomaterials; Modern structural and heat-insulating building materials